Coupling an online ion conductivity measurement with the particle-into-liquid sampler: Evaluation and modeling using laboratory and field aerosol data. Issue 12 (1st December 2020) - Crosbie, Ewan; Shook, Michael A.; Ziemba, Luke D.; Anderson, Bruce E.; Braun, Rachel A.; Brown, Matthew D.; Jordan, Carolyn E.; MacDonald, Alexander B.; Moore, Richard H.; Nowak, John B.; Robinson, Claire E.; Shingler, Taylor; et al.
Abstract: A particle-into-liquid sampler (PILS) was coupled to a flow-through conductivity cell to provide a continuous, nondestructive, online measurement in support of offline ion chromatography analysis. The conductivity measurement provides a rapid assessment of the total ion concentration augmenting slower batch-sample data from offline analysis and is developed primarily to assist airborne measurements, where fast time-response is essential. A conductivity model was developed for measured ions and excellent closure was derived for laboratory-generated aerosols (97% conductivity explained, R 2 > 0.99). The PILS-conductivity measurement was extensively tested throughout the NASA Cloud, Aerosol and Monsoon Processes: Philippines Experiment (CAMP 2 Ex) during nineteen research flights. A diverse range of ambient aerosol was sampled from biomass burning, fresh and aged urban pollution, and marine sources. Ambient aerosol did not exhibit the same degree of closure as the laboratory aerosol, with measured ions only accountable for 43% of the conductivity. The remaining fraction of the conductivity was examined in combination with ion charge balance and found to provide additional supporting information for diagnosing and modeling particle acidity. An urban plume case study was used to demonstrate the utility of the measurement for supplementing compositional data and augmenting the temporal capability of the PILS.